2022
DOI: 10.1038/s41467-022-30682-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the cardiac vascular niche in heart failure

Abstract: The cardiac vascular and perivascular niche are of major importance in homeostasis and during disease, but we lack a complete understanding of its cellular heterogeneity and alteration in response to injury as a major driver of heart failure. Using combined genetic fate tracing with confocal imaging and single-cell RNA sequencing of this niche in homeostasis and during heart failure, we unravel cell type specific transcriptomic changes in fibroblast, endothelial, pericyte and vascular smooth muscle cell subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 132 publications
2
69
0
Order By: Relevance
“…The synthesis of structural collagens, such as collagen I and collagen III, is a hallmark of fibroblasts in the healthy and remodeling heart, and Col1a1-GFP reporter mice have been a robust tool for general fibroblast identification in many organs, including the heart [ 23 ]. The indirect Cre-loxP system has also been described for the detection of collagen-producing cells in the heart [ 30 ], as well as in other organs [ 25 ]. However, we failed to detect ZsGreen reporter expression in the hearts of our Col1a1-CreERT2 animal model, either in the control or in MI hearts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of structural collagens, such as collagen I and collagen III, is a hallmark of fibroblasts in the healthy and remodeling heart, and Col1a1-GFP reporter mice have been a robust tool for general fibroblast identification in many organs, including the heart [ 23 ]. The indirect Cre-loxP system has also been described for the detection of collagen-producing cells in the heart [ 30 ], as well as in other organs [ 25 ]. However, we failed to detect ZsGreen reporter expression in the hearts of our Col1a1-CreERT2 animal model, either in the control or in MI hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy and MI mice were sacrificed one week after the last tamoxifen injection. The tamoxifen treatment procedure was followed as described in the Jax Cre Repository and as previously described in the literature [ 29 , 30 ]. Cardiotoxicity was not found at the administered doses of tamoxifen.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, other fibroblast-related genes, including those that define alternative fibroblast populations identified in single-cell RNAseq studies ( Skelly et al, 2018 ; Farbehi et al, 2019 ) were also reduced ( Figure 1I ). As PDGFRβ expressing cells are suggested to adopt fibroblast characteristics after injury ( Peisker et al, 2022 ; Henderson et al, 2013 ), we determined if the remaining collagen expressing cells were derived from a PDGFRβ population. We found that in ablated hearts PDGFRβ + cells maintained a vascular distribution similar to control hearts ( Figure 1—figure supplement 3 ) and that there was no significant increase in PDGFRβ + cells in the Col1a1- GFP + population ( Supplementary file 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts infiltrating from blood-derived progenitors, originating from pericytes, or from the endothelium through endothelial-to-mesenchymal transition have previously been reported to also contribute to cardiac myofibroblasts [ 13 , 14 , 15 ]. However, recent lineage tracing work has demonstrated that nearly all myofibroblasts post-infarction and in pressure overload arise from resident fibroblasts [ 16 , 17 , 18 ]. Myofibroblasts are the primary cells responsible for matrix synthesis in the injured heart.…”
Section: Fibroblasts Myofibroblasts and Fibrosismentioning
confidence: 99%